THE ROLE OF EMPLOYEE COMPETENCE IN IMPROVING ECONOMIC INDICATORS IN COMPANIES (Marketing Journal, 2025)
This article presents a scientific and practical analysis of the role of employee potential in improving companiesʼ economic performance. Human capital is assessed as a key strategic asset of a company, and its development is examined through KPI indicator s. Using the example of "Uzbekneftegaz" JSC, the relationship between employee efficiency and organizational economic performance is revealed. Based on the findings, practical recommendations are developed for integrating KPI systems, competency models, an d motivation mechanisms into corporate strategy.
Keywords: human capital; KPI; employee potential; economic efficiency; HR analytics; corporate strategy; motivation; competency. 351